Theology on the menu: asceticism, meat and Christian diet - Grumett, David (Routledge, 2010)
Eating in the wilderness -- Food in the ordered city -- Secularizing diet -- Fasting by choice -- Clean and unclean animals -- Community, heresy, and orthodoxy -- Sacrifice and slaughter -- Christian food, heavenly food, worldly food -- Concluding reflections